PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM CENTERED LEARNING (PCL) PADA SISWA KELAS V SD KRISTEN KIERA - Oraplean, Yosina Yokbet; Ririhena, Ribka L.; Kilikily, Cristianti C. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to find out the improvement in the skill of writing short stories on students of class V SD Kristen Kiera on the material of daily life events using the Problem Centered Learning (PCL) Model. This study is a classroom action research. The location used for this research is SD Kristen Kiera. The subjects of this research are the students of class V SD Kristen Kiera, amounting to 12 students. The improvement in the skill of writing short stories using the Problem Centered Learning (PCL) model occurred in cycle I but has not yet reached its maximum with the lower category, so it was continued to cycle ll, and there was a significant improvement in the very good category.